Inside Back Cover: From Biomass‐Derived Furans to Aromatics with Ethanol over Zeolite (Angew. Chem. Int. Ed. 42/2016). Issue 42 (6th October 2016) - Teixeira, Ivo F.; Lo, Benedict T. W.; Kostetskyy, Pavlo; Stamatakis, Michail; Ye, Lin; Tang, Chiu C.; Mpourmpakis, Giannis; Tsang, Shik Chi Edman
Abstract : Liquid lunch anyone? Ethylene produced in situ from ethanol dehydration over zeolite is used for the catalytic conversion of biomass‐derived furans into aromatic compounds by Diels–Alder cycloaddition. In their Communication onpage 13061 ff., G. Mpourmpakis, S. C. E. Tsang et al. describe a rapid and renewable one‐pot synthesis of aromatic compounds using liquid ethanol as a source of dienophile instead of pressurized ethylene gas.